Avoiding Weight Gain in Cardiometabolic Disease: A Systematic Review - Nisa M. Maruthur; Kimberly Gudzune; Susan Hutfless; Oluwakemi A. Fawole; Renee F. Wilson; Brandyn D. Lau; Cheryl A. M. Anderson; Sara N. Bleich; Jodi Segal (Hindawi Limited, 2014)
Patients with cardiometabolic disease are at higher risk for obesity-related adverse effects. Even without weight loss, weight maintenance may be beneficial. We performed a systematic review to identify the effect of nonweight loss-focused lifestyle interventions in adults with cardiometabolic disease. We searched MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials to identify comparative studies of lifestyle interventions (self-management, diet, exercise, or their combination) without a weight loss focus in adults with or at risk for diabetes and cardiovascular disease. Weight, BMI, and waist circumference at ≥12 months were the primary outcomes. Of 24,870 citations, we included 12 trials (self-management, n=2; diet, n=2; exercise, n=2; combination, n=6) studying 4,206 participants. Self-management plus physical activity ± diet versus minimal/no intervention avoided meaningful weight (−0.65 to −1.3 kg) and BMI (−0.4 to −0.7 kg/m2) increases. Self-management and/or physical activity prevented meaningful waist circumference increases versus control (−2 to −4 cm). In patients with cardiometabolic disease, self-management plus exercise may prevent weight and BMI increases and self-management and/or exercise may prevent waist circumference increases versus minimal/no intervention. Future studies should confirm these findings and evaluate additional risk factors and clinical outcomes.